Evaluation of potential punishing effects of 2,5-dimethoxy-4-methylamphetamine (DOM) in rhesus monkeys responding under a choice procedure - Maguire, David R (Behavioural pharmacology, 2024)
There has been substantial and growing interest in the therapeutic utility of drugs acting at serotonin 2A subtype (5-HT 2A ) receptors, increasing the need for characterization of potential beneficial and adverse effects of such compounds. Although numerous studies have evaluated the possible rewarding and reinforcing effects of 5-HT 2A receptor agonists, there have been relatively few studies on potential aversive effects. The current study investigated punishing effects of 2,5-dimethoxy-4-methylamphetamine (DOM) in four rhesus monkeys responding under a choice procedure in which responding on one lever delivered a sucrose pellet alone and responding on the other lever delivered a sucrose pellet plus an intravenous infusion of a range of doses of fentanyl (0.1-3.2 µg/kg/infusion), histamine (3.2-100 µg/kg/infusion), or DOM (3.2-100 µg/kg/infusion). When fentanyl was available, responding for a pellet plus an infusion increased dose dependently in all subjects, indicating a positive reinforcing effect of fentanyl. When histamine was available, responding for a pellet plus an infusion decreased in three of four subjects, indicating a punishing effect of histamine. Whether available before or after histamine, DOM did not systematically alter choice across the range of doses tested. These results suggest that the 5-HT 2A receptor agonist DOM has neither positive reinforcing nor punishing effects under a choice procedure that is sensitive to both processes.